Performance of optical displacement sensor using a pair type bundled fiber from a theoretical and experimental perspective - Yasin, M.; Harun, S. W.; Abdul-Rashid, H. A.; Zaidan, A. H. (NATL INST OPTOELECTRONICS, 2007)
An optical displacement sensor using a pair type bundled fiber is investigated from both the theoretical and experiment perspectives. The theoretical analysis uses an electromagnetic Gaussian beam approach to determine a transfer function of the sensor. The displacement between a flat mirror and the bundled fiber end is measured using an intensity modulation technique. The sensor has two operating ranges with a good linearity; namely the front slope and back slope. On the front slope the sensitivities are obtained at 1.71 and 1.0 mW/mu m for the theoretical and experimental approaches respectively while on the back slope the sensitivities are 0.38 and 0.22 mW/mu m for theoretical and experimental approaches respectively. This discrepancy in theoretical and experimental values is due to neglecting the effect of Gaussian beam truncation in our simple theoretical model. The front slope is highly sensitive and useful for close distance targets while the back slope is less sensitive and useful for large displacement movements. Document Type: Article